Site-Selective Oxidation of Vitamin B12 Using 2-Iodoxybenzoic Acid - Clardy-James, Susan; Bernstein, Jaime L.; Kerwood, Deborah J.; Doyle, Robert P. (Synlett, 2012)
Reaction of vitamin B12 (B12) with excess 2-iodoxybenzoic acid and 2-hydroxypyridine leads to selective oxidation of the 5′-hydroxyl group of the ribose tail of B12 in a 30% isolated yield. The acid derivative was purified in one step by HPLC chromatography and characterized by MALDI-TOF mass spectrometry, 1H NMR and 2D (HSQC and HMBC) NMR. The new carboxylic acid derivative is perfectly suited to make stable amide-based B12 bioconjugates.
Keywords: vitamins; oxidation; 2-iodoxybenzoic acid; carboxylic acids; cobalamin